2020
DOI: 10.1002/pan3.10132
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing bird‐keeping user‐groups on Java reveals distinct behaviours, profiles and potential for change

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 69 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…However, these numbers are supported by previous research on Java that found that only around 27% of bird-keepers owned wild-caught birds (75% owned commercially bred birds) and around 15 to 22% stated a preference for wild-caught birds (Marshall et al, 2020b, ). This said, the ubiquity of bird-ownership across Java (~12 million households; Marshall et al, 2020b) means that these proportions still represent a concerningly large number of households potentially procuring wild-caught birds in the near future. Our results suggested that social norms among bird-owners, such as peer pressure, increase intention, perhaps in accordance with other studies where ownership of wild-caught birds was clustered among socially similar communities or networks (Burivalova et al, 2017;S anchez-Mercado et al, 2020).…”
Section: Drivers Of Intention To Obtain Wild-caught Birdsmentioning
confidence: 88%
See 3 more Smart Citations
“…However, these numbers are supported by previous research on Java that found that only around 27% of bird-keepers owned wild-caught birds (75% owned commercially bred birds) and around 15 to 22% stated a preference for wild-caught birds (Marshall et al, 2020b, ). This said, the ubiquity of bird-ownership across Java (~12 million households; Marshall et al, 2020b) means that these proportions still represent a concerningly large number of households potentially procuring wild-caught birds in the near future. Our results suggested that social norms among bird-owners, such as peer pressure, increase intention, perhaps in accordance with other studies where ownership of wild-caught birds was clustered among socially similar communities or networks (Burivalova et al, 2017;S anchez-Mercado et al, 2020).…”
Section: Drivers Of Intention To Obtain Wild-caught Birdsmentioning
confidence: 88%
“…We used a structured household survey divided into demographic characteristics and bird ownership sections (see Marshall et al, 2020aMarshall et al, , 2020b and two further mixedmethods sections collecting qualitative and quantitative data (Creswell & Clark, 2007;Lecuyer et al, 2019). These additional sections gathered (a) qualitative data on reasons for starting, stopping, and not keeping birds and (b) quantitative data on respondents' attitudes and perceptions toward bird-keeping, wild bird populations, and the natural environment in general and their intention to purchase wild-caught birds in the near future (see Appendix B for full survey instrument).…”
Section: Survey Design and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of latent, potential and improbable demand, much research effort has focused on the segmentation of consumer groups (Marshall et al., 2020; Shukhova & MacMillan, 2020), a critical advance in tailoring of interventions to particular user groups and ensuring that interventions move beyond the vagueness of attempting to target the entire population under the banner of ‘general public’ (Davis et al., 2020). In this respect, the use of techniques such as choice experiments can help explore how consumer preferences would react to different scenarios.…”
Section: Understanding Demandmentioning
confidence: 99%